2012
DOI: 10.1097/sla.0b013e31824b45af
|View full text |Cite
|
Sign up to set email alerts
|

The Surgical Mortality Probability Model

Abstract: Thirty-day mortality after noncardiac surgery can be accurately predicted using a simple and accurate risk score based on information readily available at the bedside. This risk index may play a useful role in facilitating shared decision making, developing and implementing risk-reduction strategies, and guiding quality improvement efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
110
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(121 citation statements)
references
References 47 publications
(55 reference statements)
4
110
1
6
Order By: Relevance
“…1415 It has also shown modest ability to predict postoperative cardiac complications, 1130 and been an important component of models designed to predict postoperative mortality and morbidity. 6831 This consistent demonstration of moderate predictive validity by the ASA-PS scale, both in our present study and previous research, supports its use as a component of risk-adjustment models for comparing surgical outcomes across hospitals. The ASA-PS score is incorporated into the risk-adjustment model used by the National Surgical Quality Improvement Program to measure the quality of surgical care across US hospitals.…”
Section: Discussionsupporting
confidence: 90%
“…1415 It has also shown modest ability to predict postoperative cardiac complications, 1130 and been an important component of models designed to predict postoperative mortality and morbidity. 6831 This consistent demonstration of moderate predictive validity by the ASA-PS scale, both in our present study and previous research, supports its use as a component of risk-adjustment models for comparing surgical outcomes across hospitals. The ASA-PS score is incorporated into the risk-adjustment model used by the National Surgical Quality Improvement Program to measure the quality of surgical care across US hospitals.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, ISOS only included patients undergoing elective surgery. Previous mortality estimates for unselected patient populations undergoing inpatient surgery vary between 1 and 4% 15–18 . A recent study of postoperative mortality in Europe suggested in-hospital mortality of 3% for elective inpatient surgery, 11 similar to overall mortality rates in reports from the USA 9 …”
Section: Discussionmentioning
confidence: 76%
“…Each patient was assigned a Surgical Mortality Probability Model (S-MPM) risk score and class level described by Glance et al 6 The S-MPM risk score for each patient was determined from 3 risk factors: American Society of Anesthesiologists Physical Status (ASA-PS), surgical risk category, and emergency status. The point value of the score ranged from 0 to 9 and was classified into 3 levels with an associated risk of 30-day mortality assigned to each class (ie, class I: 0–4, <0.50% mortality; class II: 5–6, 1.5%−4.0% mortality; class III 7–9, >10% mortality).…”
Section: Methodsmentioning
confidence: 99%
“…The point value of the score ranged from 0 to 9 and was classified into 3 levels with an associated risk of 30-day mortality assigned to each class (ie, class I: 0–4, <0.50% mortality; class II: 5–6, 1.5%−4.0% mortality; class III 7–9, >10% mortality). 6 …”
Section: Methodsmentioning
confidence: 99%